Pengaruh Konten Tiktok Jejuby terhadap Keputusan Pembelian : Survei pada Followers Akun TikTok @jejubyofficial - Dinni Sabrina Bahri; Daniel Handoko (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the influence of Jejuby's TikTok content on the purchasing decisions of followers of the @jejubyofficial TikTok account. In today's digital age, social media platforms like TikTok have become one of the most effective promotional tools for reaching consumers, particularly in the beauty and skincare industry. Jejuby, as a local brand on the rise, actively leverages TikTok as a marketing platform by creating various types of content, including tutorials, testimonials, and visually appealing content. The theories used in this study are the Marketing Communication Theory with dimensions: Advertising, Sales Promotion, Personal Selling, Public Relations, and Direct and Digital Marketing. The Content Theory with dimensions: Credible, Shareable, Useful or Fun, Interesting, Relevant, Different, On Brand. The Purchase Decision Theory with dimensions: Need Recognition, Information Search, Evaluation of Alternatives, Purchase Decision, Post-Purchase Behavior. This study used a quantitative approach with a survey method. Sampling was conducted using simple random sampling and calculated using the Slovin formula with a margin of error of 5%. Data collection was carried out by distributing questionnaires to 92 respondents who were followers of the @jejubyofficial TikTok account. The research instrument was tested using validity and reliability tests, while data analysis was conducted using simple linear regression with a correlation coefficient (R) value of 0.711 in the strong category. The coefficient of determination (R²) value of 0.506 indicates that 50.6% of purchasing decisions are influenced by TikTok content, while 49.4% are influenced by other factors. The research results for TikTok content had an average of 3.47, while purchase decisions had an average of 3.54. The research results indicate that there is a significant influence between Jejuby's TikTok content and its followers' purchase decisions. This means that content packaged in a relevant manner and aligned with the brand's identity can influence consumers' decisions to purchase Jejuby products.